The Ritual Values of Puro Ae as a Model for Marine Conservation Based on the Local Wisdom of the Lamaojan Community - Bao Wolo, Hironimus; Wai Lawet, Pilipus; Sipa Koten, Vincentius (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
Puro Ae represents the local wisdom of the Lamaojan community in East Flores Regency, which is highly relevant in efforts to conserve the marine environment. This research aims to describe the implementation of the Puro Ae tradition, and the values embedded within it as a medium for marine conservation grounded in the local wisdom of the Lamaojan community. The data source for this research is the Puro Ae tradition. The study employed a qualitative methodology with a focus on interpretive descriptive analysis. The data consists of utterances containing marine conservation values. Data collection methods included observation and interviews with traditional elders in Lamaojan. The collected data were then reduced and analyzed using Miles and Huberman's framework. The findings reveal that: 1) Puro Ae is interpreted as the closure of the sea or the designation of a restricted marine area. There are two stages in this tradition: the "elo krowi" stage (conveying intentions and seeking blessings) and the peak ritual stage of Puro Ae; 2) the values embedded in the Puro Ae tradition include harmony, ecological awareness, life preservation, and cooperation. These values can serve as a learning model for efforts to conserve the marine environment based on local wisdom.